The Role of the Traffic Unit in Overcoming Congestion Through Traffic Engineering Management - Robby, Robbyanli Dewa Putra (Advances in Police Science Research Journal, 2024)
The background of this problem arises because the level of vehicle volume in the lembang track continues to increase. An effort is made to deal with congestion through Traffic Engineering Management. This study aims to determine whether the implementation of Traffic Engineering is optimal by the Traffic Unit. as well as factors that influence the implementation of Traffic Engineering by the Traffic Unit. Concepts and theories for analyzing the focus of research. The research concepts include the concept of Traffic Engineering and the concept of traffic congestion. Whereas the theory includes Management Function Theory (P.O.A.C) and Management Element Theory (6M). The systematic research method is a qualitative approach. This type of research is descriptive analytic. Primary and secondary data sources. Data collection techniques with interviews, observation, and document review. Its location in the Legal Area of Cimahi Police Station. Validity with triangulation. Data analysis uses data reduction and conclusions and verification. The results found that the implementation of Traffic Engineering based on Law No.22 of 2009 as a whole was optimal but there were still a few points on the implementation of Traffic Engineering in Coordination with related agencies and the organization and control and division of members in the field based on observation was not optimal. Factors affecting, among others, facilities and infrastructure, personnel, roads, public transportation, street vendors, and the community. The conclusion of the implementation of Traffic Engineering by the Cimahi Police Traffic Unit to overcome traffic congestion in the Lembang Line as regulated in Law No.22 of 2002 as a whole has been running optimally. Constructive suggestions of Traffic Engineering to overcome congestion in the Lembang Line are aimed at optimizing the handling of congestion that occurs in the Lembang Line. Constructive advice includes suggestions to further optimize the implementation of Traffic Engineering to overcome congestion in the Lembang Line by establishing targets, increasing member competencies and completing organizational structures and positions, as well as coordinating with relevant agencies and developing innovation.